The Effect Of Receivable Turnover, Current Ratio And Debt To Asset Ratio To Return On Asset In Subsector Companies Retails Registered At The Indonesia Stock Exchange Period 2016-2020 - Juliane Yukiniji (Fakultas Bisnis, 2022)
In every service company, commerce and manufacturing companies have the same goal which is to earn profit, increase company value and expand its business. In the midst of the pandemic and the intensity of business competition in the same field, every businessman should be able to fulfill the needs and operational costs of the company for its business development in order to increase the value of their company. The purpose of the study to examine the effect of receivable turnover, current ratio and debt to asset ratio to return on asset in subsector companies retail, registered on the Indonesia Stock Exchange. This study uses purposive sampling as a method sampling, which is a method that uses a sampling technique with certain considerations. The result of this study indicated that all independen variables have a significant effect on dependent variable simultaneously. Accounts receivable turnover has no effect on partial return on asset, current ratio has a positive and significant effect to return on asset partially and debt to asset ratio has a negative and significant effect to return on asset partially.